The effects of the treatment conditions on the dissolution profile of ethylcellulose coated pellets - Pavloková, Sylvie; Muselík, Jan; Sabadková, Dana; Bernatová, Silvie; Samek, Ota; Neumann, David; Franc, Aleš (European journal of pharmaceutical sciences, 2019)
Due to the additional particle coalescence in the coating, changes in the dissolution profile occur over time in the formulations coated by aqueous ethylcellulose latex. Dry thermal treatment (DT) of the coating can be used as a prevention of this process. Alternatively, it is advisable to take advantage of the synergistic effect of high humidity during wet treatment (WT), which substantially accelerates the film formation. This can be a problem for time-controlled systems, which are based on the coating rupture due to the penetration of water into the core causing the increase in the system volume. This process can begin already during the WT, which may affect the coating adversely. The submitted work was focused on the stability testing of two pellet core compositions: pellets containing swelling superdisintegrant sodium carboxymethyl starch (CMS) and pellets containing osmotically active polyethylene glycol (PEG). Another objective was to identify the treatment/storage condition effects on the pellet dissolution profiles. These pellets are intended to prevent hypoglycemia for patients with diabetes mellitus and therefore, besides the excipients, pellet cores contain 75% or 80% of glucose. The pellet coating is formed by ethylcellulose-based latex, which provides the required lag time (120-360 min). The sample stability was evaluated depending on the pellet core composition (PEG, CMS) for two types of final pellet coating treatment (DT or WT). Scanning electron microscopy and Raman microspectroscopy revealed the penetration of glucose and polyethylene glycol from the core to the PEG pellet surface after WT. For the CMS sample, significant pellet swelling after WT (under the conditions of elevated humidity) was statistically confirmed by the means of stereomicroscopic data evaluation. Therefore, the acceleration of dissolution rate during the stress tests is caused by the soluble substance penetration through the coating in the case of PEG pellets or by dosage form volume increase in the case of CMS pellets. The observed mechanisms can be generally anticipated during the stability testing of the ethylcellulose coated dosage forms. The aforementioned processes do not occur after DT and the pellets are stable in the environment without increased humidity.
Keywords: farmaceutická chemie; stabilita léku; velikost částic; hypoglykemie; vysoká teplota; škrob; Drug Implants; Particle Size; povrchové vlastnosti; Hot Temperature; Polyethylene Glycols; Stability; Chemistry, Pharmaceutical; pomocné látky; Pellet volume increase; Solubility; Drug Liberation; Drug Stability; rozpustnost; Coating penetration; příprava léků; polyethylenglykoly; léky s prodlouženým účinkem; celulosa; Delayed-Action Preparations; implantované léky; glukosa; Glucose; Starch; Excipients; Drug Compounding; uvolňování léčiv; Coated pellets; Wet treatment; Cellulose; Surface Properties; Hypoglycemia